Disturbance-induced density-dependent reproductive success in a tropical forest tree - Ghazoul, J.; Liston, K.A.; Boyle, T.J.B. (1998)
The reproductive output of Shorea siamensis, a widespread dipterocarp tree, was assessed in relation to disturbance and tree density at three sites in western Thailand during the 1996 and 1997 flowering seasons. The locations were similar except in disturbance history, which was reflected in decreasing tree density from undisturbed via moderately disturbed to disturbed sites. Hand pollination experiments showed S. siamensis to be partially self-incompatible due to differential pollen tube growth and abortion of inbred fruit. Although more than 90% of flowers from trees at all sites were pollinated, pollen tubes developed in only a small proportion of these flowers. Both pollen tube development and initial fruit production were highest at the undisturbed site. Many fruit, presumably selfed, were aborted during development at all sites, but significantly more fruit were aborted at the disturbed site, resulting in lowered production of mature fruit. S. siamensis was pollinated by small Trigona bees, which exhibited significant declines in intertree movements with increasing distance between flowering trees. As resource availability did not differ between sites, differences in mature fruit set were considered to be mediated by changes in pollinator foraging behaviour at different tree densities. Variation in seed set was negatively correlated with distance to nearest conspecific both within and between sites. At the two least disturbed sites observed seed set values corresponded with those expected by calculation. However, seed set at the disturbed site was significantly lower than expected. The results suggest that high reproductive success of S. siamensis is dependent upon cross-pollination, which, through pollinator behaviour, is a function of tree isolation. This species may thus be subject to the Allee effect, where population viability is reduced disproportionately with a decline in population size or population density. The implications of these results for population recovery and genetic structure following disturbance are discussed.